limt→∞2te−t\lim_{t\to\infty}2\sqrt{t}e^{-\sqrt{t}}t→∞lim2te−t
3x−1+1x=2\frac{3}{x-1}+\frac{1}{x}=2x−13+x1=2
3s2+14s+83s^2+14s+83s2+14s+8
d2dx2(x510−x44−17x36+15x2−1)\frac{d^2}{dx^2}\left(\frac{x^5}{10}-\frac{x^4}{4}-\frac{17x^3}{6}+15x^2-1\right)dx2d2(10x5−4x4−617x3+15x2−1)
2x+y3x+x2y−12x+\frac{y^3}{x}+\frac{x^2}{y}-12x+xy3+yx2−1
(p+3q−13z)2\left(p+3q-\frac{1}{3}z\right)^2(p+3q−31z)2
Get a preview of step-by-step solutions.
Earn solution credits, which you can redeem for complete step-by-step solutions.
Save your favorite problems.
Become premium to access unlimited solutions, download solutions, discounts and more!